2022
DOI: 10.1093/ckj/sfac057
|View full text |Cite
|
Sign up to set email alerts
|

Post-vaccination analysis of anti-spike antibody responses in kidney transplant recipients with and without COVID-19 infection in a tertiary care centre, India

Abstract: Background To investigate the anti-spike antibody response to vaccination in Kidney transplant recipients (KTRs) previously infected with SARS-CoV-2 as compared to KTRs with no history of COVID-19 from India. Methods SARS-CoV-2 spike immunoglobulin (Ig) G antibody response was measured in 105 post COVID-19 KTRs with PCR confirmed SARS-CoV-2 infection who received either no vaccination (cohort 1), single (cohort 2) or two dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Kute et al reported 61.2% seroconversion in uninfected KTRs in an Indian cohort [ 17 ]. Similarly, Jasuja et al from India reported around 49% seroconversion in a similar cohort of uninfected KTRs [ 18 ]. This difference could be related to the variation in the study population or the diagnostic assay used to detect ARAb and neutralising antibodies in these studies.…”
Section: Discussionmentioning
confidence: 92%
“…Kute et al reported 61.2% seroconversion in uninfected KTRs in an Indian cohort [ 17 ]. Similarly, Jasuja et al from India reported around 49% seroconversion in a similar cohort of uninfected KTRs [ 18 ]. This difference could be related to the variation in the study population or the diagnostic assay used to detect ARAb and neutralising antibodies in these studies.…”
Section: Discussionmentioning
confidence: 92%